Preoperative Optimization in Total Knee Arthroplasty: Beyond Weight Loss - Leja, Wiktoria; Błaszczak, Maciej; Latalska, Katarzyna; Czechowicz, Katarzyna; Szczupaj, Maciej; Pastuszak , Andżelika; Borkowski , Konrad; Rudnicki , Jakub; Zjawiony, Julia; Zulfiqar, Zeeshan (Quality in Sport, 2026)
Total knee arthroplasty is one of the most commonly performed orthopaedic surgeries worldwide. However, a significant number of patients experience post-operative complications and do not achieve satisfactory functional results after their surgical procedure. While obesity has been the main focus in pre-operative risk discussions for many years, more recent evidence indicates that there are several other modifiable factors which have equal to or greater prognostic value than obesity. This narrative review will synthesis current evidence on these same five key domains of optimization prior to surgery: glycemic control; nutritional status; physical conditioning; psychological readiness; and broader comorbidity management. Diabetes mellitus and perioperative hyperglycemia consistently have higher rates of wound dehiscence, readmission and periprosthetic joint infection. Malnourishment before surgery (up to 40% of patients undergoing arthroplasty) individually increases the risk of early implant failure and wound complications. Structured prehabilitation programs enhance functional capacity in the weeks leading up to surgery and accelerate recovery following surgery. Benefits from prehabilitation are greatest among those with the lowest levels of functional ability at baseline. Depression, anxiety, kinesiophobia and unreasonable expectations by patients are among the strongest independent predictors of poor reported outcomes and patient dissatisfaction following surgery. Finally, both preoperative anemia and smoking each contribute to adverse outcomes as well as overall comorbidity burden. The evidence supports moving away from weight-centred risk stratification towards a multidisciplinary approach to optimize all domains prior to surgery. Systematic screening for these domains and targeted intervention may result in reduced complication rates and improved reported outcomes.